Fibromyalgia increases 90-day complications and cost following primary total hip arthroplasty - Nelson, Scott R.; Polansky, Scott; Vakharia, Rushabh M.; Quattrocelli, Mathew; Devito, Paul; Cohen-Levy, Wayne; Roche, Martin W. (Annals of Joint, 2018)
Background: Fibromyalgia (FM) is known to cause chronic pain and impact multiple organ systems in addition to the musculoskeletal system. With the increasing prevalence of patients with FM undergoing primary total hip arthroplasty (THA), there is paucity in the literature regarding the impact of FM following primary THA. The purpose of the study was to compare complications in patients with and without FM undergoing primary THA, with the use of an administrative database. Methods: A retrospective review was performed using the Medicare Standard Analytical Files from the PearlDiver database. Patients undergoing primary THA were queried using the International Classification of Disease, ninth revision (ICD-9) procedure code 81.51. Inclusion criteria for the study group consisted of patients undergoing primary THA with a diagnosis of FM 90 days prior to the procedure. Patients without FM undergoing THA served as controls. Patients in the study group were matched to controls according to age, gender, and Charlson-Comorbidity Index (CCI). Two mutually exclusive cohorts were formed and outcomes analyzed and compared included medical and implant complications, 90-day readmission rates, and cost. Statistical analysis was performed using to calculate odds-ratios (OR), 95% confidence intervals (95% CI), and their respective P values. Results: After the matching process 152,206 patients were identified with (n=76,103) and without FM (n=76,103) undergoing primary THA. FM patients had greater odds of developing medical complications (2.88% vs. 1.43%; OR: 2.05; P